Avaliação do efeito da fotobiomodulação das glândulas salivares maiores no fluxo e bioquímica salivar de pacientes com insuficiência renal crônica: ensaio clínico, randomizado e controlado - Pavesi, Vanessa Christina Santos (2018)
The patient with chronic renal failure (CRF) presents with a series of important systemic and oral complications. Among the most frequent oral complications are xerostomia. The treatment for salivary changes remains unknown, but the low-intensity laser has been shown to be efficient in improving salivary flow in patients with xerostomia due to diabetes, Sjogrem's syndrome and patients on chemotherapy and radiotherapy for head cancer and neck. This randomized controlled trial aims to evaluate buccal symptoms related to salivary gland function and mucosal condition of patients with chronic renal failure on hemodialysis, in addition to the effect of photobiomodulation on the salivary flow, 38 patients with CRF on hemodialysis , after signing the Free and Informed Consent Term, were submitted to anamnesis, physical evaluation and self-perception questionnaires of oral health and symptoms related to the function of the salivary glands and were then divided into two groups: Photobiomodulated (PBM) (n = 21); (808 nm, 4J per point, 40 s) and placebo (PCB) (n = 17), which were submitted to a simulation, where the application protocol was repeated, but with the laser off, we performed previous sialometries and post treatment to compare the volume of saliva and the biochemical analysis, where we measured total proteins, calcium and urea. Analyzing the self- perception questionnaire, 52% of the patients related their dental problems with chronic kidney disease and the complaint of dry mouth was the most frequent (n = 26). The PBM group presented a significant increase of the salivary flow, unlike the PCB group. Regarding salivary biochemistry, there were no differences between total protein and calcium dosages and a decrease in the urea dosage when compared to saliva before and after photobiomodulation and no differences were observed in the PCB group. We conclude that this protocol of salivary gland photobiomodulation significantly increased the flow and decreased the salivary urea concentration of patients with CRF, but did not alter the total protein and saliva calcium dosage.